2021
DOI: 10.1155/2021/6639602
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Mechanical Properties and Micromechanism of Calcareous Sand Modified by Nanoclay and Cement

Abstract: Calcareous sand is developed by the fracture of marine biological skeleton under the impact of seawater. Calcareous sand is not transported in the process of deposition. Therefore, calcareous sand retains the characteristics of marine biological skeleton, low strength, and porous. In order to study the effect of nanoclay and cement on the modification of calcareous sand, a series of tests were carried out on the modified cement calcareous sand (CCS) with different content of nanoclay. In this study, the triaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The results show that GO is easy to interact with calcareous sand, thus affecting its environmental behavior. At the same time, calcareous sand is widely used as a construction material [55], and it is therefore foreseeable that the addition of calcareous sand as a construction material in the construction of GO contaminated sites could also adsorb GO from contaminated sites to avoid GO harming human health through the water cycle, indicating that the adsorption potential of calcareous sand for GO is very high.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that GO is easy to interact with calcareous sand, thus affecting its environmental behavior. At the same time, calcareous sand is widely used as a construction material [55], and it is therefore foreseeable that the addition of calcareous sand as a construction material in the construction of GO contaminated sites could also adsorb GO from contaminated sites to avoid GO harming human health through the water cycle, indicating that the adsorption potential of calcareous sand for GO is very high.…”
Section: Discussionmentioning
confidence: 99%
“…During backfill mining, nanocomposite fiber-CPB with improved mechanical properties can fully alleviate the migration of the overburden and effectively control the deformation of roadway-surrounding rock. For example, carbon nanotubes (CNTs) can be used to alter the damage degree of the cement matrix and increase the chemical energy of the material, leading to a significant improvement in the compressive strength of the cement matrix [20]. In addition, polypropylene fibers can be used to modify rubber tailings and waste rock fillers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied the mechanical properties of nano-clay and cement composite-modified calcareous sand reinforcement or binder materials, such as cement, fiber, fly ash, and curing agent, ar often used to improve soils' strength and stiffness characteristics [13][14][15][16][17][18][19][20][21][22][23][24][25]. Wang et al stud ied the mechanical properties of nano-clay and cement composite-modified calcareou sand through triaxial unconsolidated undrained and scanning electron microscope tests and found that nano-clay could modify the shear properties of cement calcareous san [26]. Zhang et al investigated the unconfined compressive strength and stiffness of so reinforced with a combination of fibers and lime, and found that the optimum fiber con tent was 1% [27].…”
Section: Introductionmentioning
confidence: 99%